2015
DOI: 10.3390/s150614370
|View full text |Cite
|
Sign up to set email alerts
|

Managing Emergency Situations in the Smart City: The Smart Signal

Abstract: In a city there are numerous items, many of them unnoticed but essential; this is the case of the signals. Signals are considered objects with reduced technological interest, but in this paper we prove that making them smart and integrating in the IoT (Internet of Things) could be a relevant contribution to the Smart City. This paper presents the concept of Smart Signal, as a device conscious of its context, with communication skills, able to offer the best message to the user, and as a ubiquitous element that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
0
14
0
12
Order By: Relevance
“…It is a part of a smart city project that allows various departments and entities to collaborate, particularly when dealing with emergency situations. The emergency system is inspired by smart city projects to manage disaster situations by encompassing modern IoT and CPS technologies [62], [63] as CPSoS (consisting of various IoT-based CPS nodes and third party independent CSs). emergency response SoS, in collaboration with remotely distributed software-intensive systems, deals specifically with sudden fire eruptions in urban and rural areas with continuous monitoring.…”
Section: Case Study-emergency Response System As Cpsos Using Hsfmentioning
confidence: 99%
“…It is a part of a smart city project that allows various departments and entities to collaborate, particularly when dealing with emergency situations. The emergency system is inspired by smart city projects to manage disaster situations by encompassing modern IoT and CPS technologies [62], [63] as CPSoS (consisting of various IoT-based CPS nodes and third party independent CSs). emergency response SoS, in collaboration with remotely distributed software-intensive systems, deals specifically with sudden fire eruptions in urban and rural areas with continuous monitoring.…”
Section: Case Study-emergency Response System As Cpsos Using Hsfmentioning
confidence: 99%
“…This value represents only 1% of the battery self-discharge rate (8–10% capacity/month, i.e., 277.5 mWh/week). In a long-term monitoring configuration, the expected operating cycle can be calculated by making an acceptable approximation in considering the electric consumptions as zero and concerning only the battery shelf life [ 22 , 23 ].…”
Section: Proposed Shm Systemmentioning
confidence: 99%
“…He concluded that the HAP network architecture could be fitted with telecommunications equipment and used to support these critical communications missions when a catastrophic event occurred. Asensio et al [ 14 ] presented a smart emergency signaling system architecture for tunnels and large infrastructures in smart city scenarios, which significantly improves the actual functionality of the signal. Aranti et al [ 15 ] investigated how the HAP network architecture effectively supports multimedia broadcast/multicast service (MBMS) in a scenario where the existing terrestrial network infrastructure is not available.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Lin et al [ 16 ] described the design and implementation of a proof-of-concept prototype, named the active disaster response system (ADRS), which automatically performs emergency tasks when an earthquake happens. In [ 12 , 13 , 14 , 15 , 16 ], the authors provide a number of different architectures for emergency networks. However, there are quite a few works in the literature that emphasize the IHS architecture’s suitability for emergency communications.…”
Section: Motivation and Related Workmentioning
confidence: 99%